Content of nutrients and limitation of phytoplankton primary production in the specially protected natural area “Cape Martyan” (Black Sea) - V. N. Egorov (A. O. Kovalevsky Institute of Biology of the Southern Seas of RAS, 2021)
The results are presented of studying the content of nitrogen compounds and mineral phosphorus, as well as phytoplankton primary production (PPP). The research was carried out in 2017–2019 in the marine area of the specially protected natural area “Cape Martyan” located on the southern coast of Crimea (Black Sea). As found, during summer in the surface seawater layer, PPP can be limited by both nitrogen and phosphorus. The dependence of PPP variation on the concentration of total nitrogen in water is not significant, while the dependence on the concentration of phosphorus is significant. It is shown that during the entire annual cycle, concentrations of nitrites, nitrates, ammonium, and mineral phosphorus vary but remain within the limits that do not lead to water hypereutrophication. A high ecological significance of precipitation was revealed: the related increase in PO4 concentration caused a transition in PPP limitation mode from phosphorus to nitrogen one. Using theoretical concepts, it is substantiated that, under oligotrophic conditions, an increase in the concentration of the substrate limiting PPP in water results in an increase in the rate of its uptake from the environment in accordance with the negative feedback of natural regulation of ecosystem homeostasis. Under conditions of eutrophication, the effect of production processes on water conditioning by the factor of nutrients decreases.